Review on Project Management - Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
Every single one of us is project manager. This paper all work on various tasks with deadlines, from a housewife to a production employee to a financial analyst, from banker to physician, from engineer to administrator, from teacher to student. Regardless of our profession, training or position within an organization, this paper work on special projects involving people who do not normally work together. The project may have a simple goal that doesn't require a lot of people or a lot of money, or it can be very complicated, calling for different skills and a lot of resources. But the bottom line is that each of us is running projects. Over the years, and more specifically in recent past ventures, this has been used as a delivery mechanism for doing business and achieving goals. No wonder this has become one of the world's fastest growing occupations. Though understanding what constitutes a project and what does not remain a topic of discussion. This paper aims to find literature about the project, its description, its features, its life cycle, stages, methods etc.